Une leçon à apprendre ? Le Parti Communiste Italien face au coup d’État chilien de 1973 - Roberto Colozza (Nuevo mundo - Mundos Nuevos, 2021)
The article analyzes what impact had the co p d’Etat in Chile of September 1973 on the Italian communist party (PCI). Due to its similarity with Italy, Chile was a familiar case-study for the PCI as well as a country where the Italian party had significant interconnections. The golpe was a shock, but also a source of reflection for Enrico Berlinguer and his comrades. PCI’s main goal was to prevent Italy from experiencing the conditions that have allowed a military government to seize power. The Unidad Popular’s worse error was particularly feared, which was its lack of collaboration with the Christian democrats, hence its isolation and vulnerability. PCI’s reaction was a strategic proposal – the compromesso storico – to bring together Communists, Socialists and Christian democrats against rightist terrorism in Italy (strategy of tension). Moreover, the article examines the PCI’s initiatives to help Chilean exiles and the fight against Augusto Pinochet’s dictatorship.